(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article comprehensively examines the issues of improving independent learning tasks in teaching Uzbek literature. The content of the tasks, factors for increasing their effectiveness, and ways of developing them based on modern pedagogical approaches were analyzed. Special attention was also paid to the issues of dividing tasks into stages, introducing digital technologies, and improving the assessment system.